2014
DOI: 10.1080/1369118x.2014.984743
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlinking practices in Swedish online news 2007–2013: the rise, fall, and stagnation of hyperlinking as a journalistic tool

Abstract: Hyperlinks are considered vital to both the Web and to digital journalism. This study utilizes a longitudinal content analysis of hyperlinking practices in Swedish online news from 2007 to 2013 to see how hyperlinking evolves over time. It also compares if and to what extent publishing tradition shapes journalistic practice. The findings primarily show that the overall impact of hyperlinks remains largely unchanged over time but that internal links, while still being most common, decrease in relative importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 42 publications
(111 reference statements)
0
9
0
1
Order By: Relevance
“…But due to the crisis affecting the media industry worldwide (Pew Research Center, ; Newman et al, ), business criteria tend to dominate journalistic decisions. As a consequence, news sites rarely link to external competitors: They treat links not as journalistic objects that add value to the stories, but as economic assets or functional devices that can, in principle, keep audiences within corporate boundaries (Dimitrova, Connolly‐Ahern, Williams, Kaid, & Reid, ; Karlsson, Clerwall, & Örnebring, ). The “link tax” that motivates this study, and the lobbying efforts that underlie its political sponsorship, are a good example of how business criteria dominate journalistic decisions – and of how the industry is trying to monetize emerging patterns of news consumption.…”
Section: Digital News Consumptionmentioning
confidence: 99%
“…But due to the crisis affecting the media industry worldwide (Pew Research Center, ; Newman et al, ), business criteria tend to dominate journalistic decisions. As a consequence, news sites rarely link to external competitors: They treat links not as journalistic objects that add value to the stories, but as economic assets or functional devices that can, in principle, keep audiences within corporate boundaries (Dimitrova, Connolly‐Ahern, Williams, Kaid, & Reid, ; Karlsson, Clerwall, & Örnebring, ). The “link tax” that motivates this study, and the lobbying efforts that underlie its political sponsorship, are a good example of how business criteria dominate journalistic decisions – and of how the industry is trying to monetize emerging patterns of news consumption.…”
Section: Digital News Consumptionmentioning
confidence: 99%
“…Nevertheless, an excellent longitudinal study of hyperlinks at four leading Swedish newspapers found that external hyperlinks often 'linked to other businesses within the same parent corporation and also to business collaborations with external partners' (Karlsson, Clerwall, & Örnebring, 2015, p. 860, italics mine). Contrary to Deuze (2003), Karlsson et al (2015) suggest that offsite external hyperlinks may be governed by protectionist marketing incentives, and may therefore be similar to internal hyperlinks. In order to survive the transition from print to digital publishing, newspaper industries have adopted new business models that rely on streams of revenue unrelated to the journalistic activities of the organization such as partnerships with web shops, telecommunications and other services (Villi & Hayashi, 2015).…”
Section: Literature Reviewmentioning
confidence: 92%
“…In order to survive the transition from print to digital publishing, newspaper industries have adopted new business models that rely on streams of revenue unrelated to the journalistic activities of the organization such as partnerships with web shops, telecommunications and other services (Villi & Hayashi, 2015). Therefore, despite the rise of external links observed by Karlsson et al (2015), the question remains whether external links to affiliated websites add value to the original content in terms of source transparency, credibility and diversity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations